Characterization of engraftment dynamics in myelofibrosis after allogeneic hematopoietic cell transplantation including novel conditioning schemes - Jungius, Sarah; Adam, Franziska C.; Grosheintz, Kerstin; Medinger, Michael; Buser, Andreas; Passweg, Jakob R.; Halter, Jörg P.; Meyer, Sara C. (Frontiers in Oncology, 2023)
Myelofibrosis (MF) is a rare hematopoietic stem cell disorder progressing to bone marrow (BM) failure or blast phase. Allogeneic hematopoietic cell transplantation (HCT) represents a potentially curative therapy for a limited subset of patients with advanced MF, who are eligible, but engraftment in MF vs.AML is delayed which promotes complications. As determinants of engraftment in MF are incompletely characterized, we studied engraftment dynamics at our center.A longitudinal cohort of 71 allogeneic HCT performed 2000-2019 with >50% after 2015 was evaluated.Median time to neutrophil engraftment ≥0.5x10 9 /l was +20 days post-transplant and associated with BM fibrosis, splenomegaly and infused CD34+ cell number. Engraftment dynamics were similar in primary vs. secondary MF and were independent of MF driver mutations in JAK2, CALR and MPL. Neutrophil engraftment occurred later upon haploidentical HCT with thiotepa-busulfan-fludarabine conditioning, post-transplant cyclophosphamide and G-CSF (TBF-PTCy/G-CSF) administered to 9.9% and 15.6% of patients in 2000-2019 and after 2015, respectively. Engraftment of platelets was similarly delayed, while reconstitution of reticulocytes was not affected.Since MF is a rare hematologic malignancy, this data from a large number of HCT for MF is essential to substantiate that later neutrophil and platelet engraftment in MF relates both to host and treatmentrelated factors. Observations from this longitudinal cohort support that novel conditioning schemes administered also to rare entities such as MF, require detailed evaluation in larger, multi-center cohorts to assess also indicators of long-term graft function and overall outcome in patients with this infrequent hematopoietic neoplasm undergoing allogeneic transplantation.